2016
DOI: 10.18632/oncotarget.11040
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a-5p inhibits cell proliferation and cell cycle progression in NSCLC cell lines by targeting CCND1 and CCND2

Abstract: Previous studies have indicated that miR-146a-5p acts as an oncogene in several types of cancer, yet a tumor suppressor gene in others. In non-small cell lung cancer (NSCLC), one report showed that it was downregulated and played the role of tumor suppressor. However, another study showed that miR-146a-5p was overexpressed in the serum of NSCLC patients compared to healthy controls. Therefore, it is obvious that further study of the function of miR-146a-5p in NSCLC is necessary to fully understand its importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 38 publications
8
71
2
Order By: Relevance
“…miR-146a-5p functions as a tumor suppressor in various types of cancer, including hepatocellular carcinoma, esophageal squamous cell carcinoma, NSCLC and prostate cancer (20)(21)(22)(23). However, the role of miR-146a-5p in the development of TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-146a-5p functions as a tumor suppressor in various types of cancer, including hepatocellular carcinoma, esophageal squamous cell carcinoma, NSCLC and prostate cancer (20)(21)(22)(23). However, the role of miR-146a-5p in the development of TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (21) revealed that miR-146a-5p promoted esophageal squamous cell carcinoma progression by regulating epithelial-mesenchymal transition (EMT) via targeting Notch2. Furthermore, miR-146a-5p has been confirmed to inhibit non-small cell lung cancer (NSCLC) cell proliferation and cell cycle progression (22). Another study indicated that miR-146a-5p could promote prostate cancer cell apoptosis by targeting ROCK1 (23).…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a is a potent suppressor of inflammation4243, including the suppression of cigarette smoke-induced COX-2 in vitro 23. As such, miR-146a may play an important role in inflammation-associated diseases such COPD2444, lung cancer4546 and CVD47. There is evidence that miR-146a is transiently induced by inflammatory stimuli, including smoke exposure, where there is a rapid rise followed by a return to basal levels with 24 hours or so4048.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, patients with low miR‐146a expression in their lung tumors tended to have advanced stage cancer and metastases, while patients with high miR‐146a levels demonstrated longer progression‐free survival (Chen et al, ). Cell cycle progression is also slowed by miR‐146a, in part by specifically targeting cyclins D1/2 (Li et al, ) and cyclin J (Shi et al, ). These in vitro results were replicated in a xenograft mouse model, where implanted cells overexpressing miR‐146a formed smaller tumors (Li et al, ).…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%